Degradation of Diatom Protein in Seawater: A Peptide-Level View - Duffy, Megan E.; Adams, Cheyenne M.; Homolka, Khadijah K.; Neibauer, Jacquelyn A.; Mayer, Lawrence M.; Keil, Richard G. (Frontiers in Marine Science, 2022)
Peptides and proteins were identified during a controlled laboratory degradation of the marine diatom Thalassiosira weissflogii by a surface seawater microbiome. Samples from each time point were processed both with and without the protease trypsin, allowing a partial differentiation between peptides produced naturally by microbial enzymatic degradation and peptides produced from the laboratory digestion of intact protein. Over the 12-day degradation experiment, 31% of the particulate organic carbon was depleted, and there was no preferential degradation of the overall protein pool. However, there was distinct differentiation in the cellular location, secondary structure and modifications between peptides produced by microbial vs. laboratory breakdown. During the initial period of rapid algal decay and bacterial growth, intracellular components from the cytoplasm were consumed first, resulting in the accumulation of membrane-associated proteins and peptides in the detrital pool. Accompanying the enrichment of membrane protein material was an increase in the importance of ɑ-helix motifs. Methylated arginine, a post-translational modification common in cell senescence, was found in high amounts within the microbially-produced detrital peptide pool, suggesting a link between in-cell modification and resistance to immediate degradation. Another modification - asparagine deamidation - accumulated within the detrital peptides. Protein taxonomies showed the bacterial community decomposing the algal material was rich in Proteobacteria, and protein annotations showed abundant transportation of solubilized carbohydrates and small peptides across membranes. At this early stage of diagenesis, no changes in bulk amino acids (THAA) were observed, yet a proteomic approach allowed us to observe selective changes in diatom protein preservation by using amino acid sequences to infer subcellular location, secondary structures, and post-translational modifications.